Janus-like Hollow Polymer Spheres Prepared from Emulsion Droplets by the Solvent Evaporation Method - Deng, Yi; Li, Bo; Yin, Qinjian; Jiang, Bo (Asian Journal of Chemistry, 2012)
Polystyrene/poly(vinylbenzylchloride) hollow spheres with Janus-like morphology were produced from emulsion droplets via evaporation of the organic solvent followed by extraction of internal phase water. The effect of the organic solvent and the weight ratio of polystyrene: poly(vinylbenzylchloride) on the morphology were discussed. Benzene, 1,2-dichloroethane (1,2-DCE), fluorobenzene, benzene-1,2-dichloroethane mixture were used as oil phase solvent respectively and variety of polymer with different weight ratio of polystyrene/ poly(vinylbenzylchloride) were tested. When benzene-1,2-dichloroethane mixture used as oil phase solvent and the weight ratio of polystyrene: poly(vinylbenzylchloride). Solvent fixed at 2:4:94, the obtained hollow spheres formed the morphology of Janus-like. The two-dimensional infrared images results showed the hollow spheres generated polystyrene-rich and poly(vinylbenzylchloride)-rich hemispheres.